Self-directed learning versus traditional didactic learning in undergraduate medical education: a systemic review and meta-analysis - Jasmine Aulakh; Hana Wahab; Christine Richards; Satesh Bidaisee; Prakash V. A. K Ramdass (BMC Medical Education)
Abstract Background Self-Directed Learning (SDL) is a theory of andragogy in which adult learners take their own initiative to identify and tailor their individual learning process and outcomes. In undergraduate medical education, SDL aims to develop medical students into lifelong learners. This study aims to estimate the overall effectiveness of self-directed learning compared to traditional didactic learning (TDL). Methods We performed a systematic review and meta-analysis according to the PRISMA statement. A systematic search was used across PubMed, Scopus, Embase and Google Scholar to identify peer-reviewed articles spanning from January 1, 2014, to May 30, 2024. Key words used were “self-directed learning” AND “undergraduate medical education.” Forest plots were generated with the Open Meta-analyst Software, comparing SDL and TDL. Results A total of 2,955 titles and abstracts were screened for eligibility, of which 95 articles met the eligibility criteria for full-text review. Following a more detailed screening, 19 articles met the criteria for inclusion in the systematic review and 14 articles met the criteria for inclusion in the meta-analysis. The systematic review included 2,098 students while the meta-analysis included 1,792 students. The overall mean difference for all studies was 2.399, 95% CI [0.121–4.678], and I2 = 98.56%. Conclusion Self-directed learning compared to traditional didactic learning is an effective learning strategy in medical undergraduate education and has the potential to aid in students’ learning and improve their cognitive performance. Moreover, SDL nurtures qualities such as autonomy, curiosity, and self-regulation, which are essential for success in the ever-evolving field of medicine.